Hallucinations in the general population across the adult lifespan: prevalence and psychopathologic significance. (December 2021) - Yates, Kathryn; Lång, Ulla; Peters, Evyn M.; Wigman, Johanna T. W.; McNicholas, Fiona; Cannon, Mary; DeVylder, Jordan; Ramsay, Hugh; Oh, Hans; Kelleher, Ian
Abstract : Background: Community studies have found a relatively high prevalence of hallucinations, which are associated with a range of (psychotic and non-psychotic) mental disorders, as well as with suicidal ideation and behaviour. The literature on hallucinations in the general population has largely focused on adolescents and young adults. Aims: We aimed to explore the prevalence and psychopathologic significance of hallucinations across the adult lifespan. Method: Using the 1993, 2000, 2007 and 2014 cross-sectional Adult Psychiatric Morbidity Survey series ( N = 33 637), we calculated the prevalence of past-year hallucinations in the general population ages 16 to ≥90 years. We used logistic regression to examine the relationship between hallucinations and a range of mental disorders, suicidal ideation and suicide attempts. Results: The prevalence of past-year hallucinations varied across the adult lifespan, from a high of 7% in individuals aged 16–19 years, to a low of 3% in individuals aged ≥70 years. In all age groups, hallucinations were associated with increased risk for mental disorders, suicidal ideation and suicide attempts, but there was also evidence of significant age-related variation. In particular, hallucinations in older adults were less likely to be associated with a cooccurring mental disorder, suicidal ideation or suicide attempt compared with early adulthood and middle age. Conclusions: Our findings highlight important life-course developmental features of hallucinations from early adulthood to old age.